Spironolactone as an alternative way of treating acne in women - review - Gajkiewicz, Magdalena; Zaucha, Radosław; Felińska, Zuzanna; Fura, Tomasz; Silldorff, Julia; Dudek, Marcin; Zając, Małgorzata; Iszczuk, Oliwia; Anczyk, Stanisław (Quality in Sport, 2024)
Introduction and objective: This paper provides an in-depth exploration of the pharmacology of spironolactone, elucidating its mechanisms of action and clinical implications beyond its conventional indications. Additionally, it examines the pathogenesis, clinical presentation, and current treatment strategies for acne vulgaris, contextualizing spironolactone's role in acne management. Review methods: Electronic searches were conducted between 15 and 26 April 2024 and included databases: Pubmed and Google Scholar. The following trials registers were searched using the search terms “spironolactone” AND “acne”. This review focuses on 3 trials that are limited to years 2020-2024. Brief description of state of knowledge: Acne vulgaris is a prevalent chronic inflammatory skin condition characterized by sebaceous gland hyperactivity, follicular hyperkeratinization, microbial colonization, and inflammation. Despite the availability of numerous treatment modalities, therapeutic success can be challenging, particularly in cases of hormonal or treatment-resistant acne. Spironolactone, initially developed as an aldosterone antagonist, has emerged as an off-label option for acne management, especially in individuals with hormonal influences on their condition. Summary: In light of conflicting recommendations regarding spironolactone's use in acne management, this review aims to provide a comprehensive synthesis of current evidence, guiding its judicious use in clinical practice. By bridging pharmacological insights with clinical data, this paper contributes to a deeper understanding of spironolactone's influence in the treatment landscape of acne vulgaris.